A biometric and PUF-based authentication with Preserving anonymity in smart grid environment - E. Haodudin Nurkifli (Ain Shams Engineering Journal, 2024)
The intelligent grid environment is an electricity transmission and distribution system utilizing information and communication technology with two main components: the Smart Meter (SM) and the Service Provider (SP). Unfortunately, wireless mode communication allows the attacker to get data from the public channels and then alter, delete the data, and perform a severe attack such as DoS, impersonation, and tracking attack. In addition, the smart meter is vulnerable to cloning attacks. This research proposes a new authentication protocol utilizing Biometrics and Physical Unclonable Function (PUF). Intuitive analysis DY model ensures our protocol successfully attains security properties and withstands well-known attacks; formal analysis using mathematical and programming models such as Mao-and-Boyd Logic, Real-or-Random Model, and Scyther tools prove that our protocol also satisfies security features and resists well-known attacks. Subsequently, computational complexity comparisons are carried out to prove that our proposal has a low computational burden.